RPA complexes in Caenorhabditis elegans meiosis; unique roles in replication, meiotic recombination and apoptosis. Issue 4 (21st January 2021) - Hefel, Adam; Honda, Masayoshi; Cronin, Nicholas; Harrell, Kailey; Patel, Pooja; Spies, Maria; Smolikove, Sarit
Abstract: Replication Protein A (RPA) is a critical complex that acts in replication and promotes homologous recombination by allowing recombinase recruitment to processed DSB ends. Most organisms possess three RPA subunits (RPA1, RPA2, RPA3) that form a trimeric complex critical for viability. The Caenorhabditis elegans genome encodes RPA-1, RPA-2 and an RPA-2 paralog RPA-4. In our analysis, we determined that RPA-2 is critical for germline replication and normal repair of meiotic DSBs. Interestingly, RPA-1 but not RPA-2 is essential for somatic replication, in contrast to other organisms that require both subunits. Six different hetero- and homodimeric complexes containing permutations of RPA-1, RPA-2 and RPA-4 can be detected in whole animal extracts. Our in vivo studies indicate that RPA-1/4 dimer is less abundant in the nucleus and its formation is inhibited by RPA-2. While RPA-4 does not participate in replication or recombination, we find that RPA-4 inhibits RAD-51 filament formation and promotes apoptosis of a subset of damaged nuclei. Altogether these findings point to sub-functionalization and antagonistic roles of RPA complexes in C. elegans .